On-Demand Intraoperative 3-Dimensional Printing of Custom Cranioplastic Prostheses. Issue 3 (13th January 2018) - Evins, Alexander I; Dutton, John; Imam, Sayem S; Dadi, Amal O; Xu, Tao; Cheng, Du; Stieg, Philip E; Bernardo, Antonio
Abstract: BACKGROUND: Currently, implantation of patient-specific cranial prostheses requires reoperation after a period for design and formulation by a third-party manufacturer. Recently, 3-dimensional (3D) printing via fused deposition modeling has demonstrated increased ease of use, rapid production time, and significantly reduced costs, enabling expanded potential for surgical application. Three-dimensional printing may allow neurosurgeons to remove bone, perform a rapid intraoperative scan of the opening, and 3D print custom cranioplastic prostheses during the remainder of the procedure. OBJECTIVE: To evaluate the feasibility of using a commercially available 3D printer to develop and produce on-demand intraoperative patient-specific cranioplastic prostheses in real time and assess the associated costs, fabrication time, and technical difficulty. METHODS: Five different craniectomies were each fashioned on 3 cadaveric specimens (6 sides) to sample regions with varying topography, size, thickness, curvature, and complexity. Computed tomography-based cranioplastic implants were designed, formulated, and implanted. Accuracy of development and fabrication, as well as implantation ability and fit, integration with exiting fixation devices, and incorporation of integrated seamless fixation plates were qualitatively evaluated. RESULTS: All cranioprostheses were successfully designed and printed. Average time for design, from importation of scan data to initiation of printing, was 14.6 min and average print time for all cranioprostheses was 108.6 min. CONCLUSION: On-demand 3D printing of cranial prostheses is a simple, feasible, inexpensive, and rapid solution that may help improve cosmetic outcomes; significantly reduce production time and cost—expanding availability; eliminate the need for reoperation in select cases, reducing morbidity; and has the potential to decrease perioperative complications including infection and resorption.